Molecular epidemiology of an extended multiple-species OXA-48 CPE outbreak in a hospital ward in Ireland, 2018-2019 - Carina Brehony; Lisa Domegan; Margaret Foley; Margaret Fitzpatrick; Jacqueline P. Cafferkey; Karina O'Connell; Binu Dinesh; Eleanor McNamara; Fionnuala Duffy; Fidelma Fitzpatrick; Karen Burns (Cambridge University Press, 2021)
Abstract Objectives: Molecular epidemiological description of an OXA-48 CPE outbreak affecting a tertiary-care hospital ward in Ireland over an extended period (2018-2019). Methods: Microbiological testing and whole-genome sequencing (WGS) were performed on all 56 positive OXA-48 outbreak case isolates. Results: In total, 7 different species were identified: Enterobacter hormaechei (n = 35, 62.5%), Escherichia coli (n = 12, 21.4%), Klebsiella pneumoniae (n = 5, 8.9%), Klebsiella oxytoca (n = 1, 1.8%), Klebsiella michiganensis (n = 1, 1.8%), Citrobacter freundii (n = 1, 1.8%), and Serratia marcesens (n = 1, 1.8%). E. hormaechei ST78 was the most common genotype (n = 14, 25%). Two major pOXA-48 plasmid types were identified throughout the outbreak, 'types' 1 and 2, and 5 major E. hormaechei clonal groupings were identified: ST78, ST108, ST1126, ST135, and ST66. Within each of the ST108, ST1126, ST135 and ST66 groups, the pOXA-48 harbored within each isolate were the same. Within ST78, 9 isolates contained the pOXA48 'type 2' plasmid and 5 contained the 'type 1' plasmid. Environmental specimens were taken from different outbreak ward locations: handwash basins, sink and shower drains, and taps. Of 394 environmental specimens, OXA-48 CPE was isolated from 26 (6.6%). Conclusions: This prolonged outbreak of OXA-48 CPE was confined to one ward, but it exemplifies the complexity and difficulty in the control of these organisms. With multiple species and genotypes involved, they may be better described as 'plasmid outbreaks.' WGS provided insights into this diversity and potential transmission among cases, though its usefulness would be enhanced by analysis as close as possible to real time so that interventions can be implemented as soon as data are available.